Competencias digitales para los ciudadanos del siglo XXI - García Sandoval, Claudia (2013)
This article has the purpose to introduce the Digital Competence termas one of the key competences for the permanent learning; basic andfundamental competence in the XXI century society.In addition, it is performed a presentation of central aspects of theFinal Report of DIGCOMP (Digital Competence) Project which iselaborated for the European Union by identifying five areas of theDigital Competence, as well as a list of descriptors for each one. Finally,it is made a reflection about the importance of its development and it issuggested a personal self-assessment in this competence